Advance in sex differentiation in cucumber - Luo, Haiyan; Zhang, Huanchun; Wang, Huasen (Frontiers in Plant Science, 2023)
Cucumber belongs to the family Cucurbitaceae (melon genus) and is an annual herbaceous vegetable crop. Cucumber is an important cash crop that is grown all over the world. From morphology to cytology, from canonical genetics to molecular biology, researchers have performed much research on sex differentiation and its regulatory mechanism in cucumber, mainly in terms of cucumber sex determination genes, environmental conditions, and the effects of plant hormones, revealing its genetic basis to improve the number of female flowers in cucumber, thus greatly improving the yield of cucumber. This paper reviews the research progress of sex differentiation in cucumber in recent years, mainly focusing on sex-determining genes, environmental conditions, and the influence of phytohormones in cucumber, and provides a theoretical basis and technical support for the realization of high and stable yield cultivation and molecular breeding of cucumber crop traits.